A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini) - Cole, Jeffrey A.; Weissman, David B.; Lightfoot, David C.; Ueshima, Norihiro; Warchałowska-Śliwa, Elżbieta; Maryańska-Nadachowska, Anna; Chatfield-Taylor, Will (Zootaxa, 2021)
The Nearctic shield-back katydid genus Neduba is revised. Species boundaries were demarcated by molecular phylogenetic analysis, morphology, quantitative analysis of calling songs, and karyotypes. Nine previously described species are redescribed: N. carinata, N. castanea, N. convexa, N. diabolica, N. extincta, N. macneilli, N. propsti, N. sierranus, and N. steindachneri, and twelve new species are described: N. ambagiosa sp. n., N. arborea sp. n., N. cascadia sp. n., N. duplocantans sp. n., N. inversa sp. n., N. longiplutea sp. n., N. lucubrata sp. n., N. oblongata sp. n., N. prorocantans sp. n., N. radicata sp. n., N. radocantans sp. n., and N. sequoia sp. n. We chose a lectotype for N. steindachneri and transferred N. picturata from a junior synonym of N. diabolica to a junior synonym of N. steindachneri. Diversification in this relict group reflects cycles of allopatric isolation and secondary contact amidst the tumultuous, evolving geography of western North America. The taxonomy and phylogenies presented in this revision lay the groundwork for studies of speciation, biogeography, hybrid zones, and behavioral evolution. Given that one Neduba species is already extinct from human environmental disturbance, we suggest conservation priorities for the genus.